Effects of very low volume high intensity versus moderate intensity interval training in obese metabolic syndrome patients: a randomized controlled study - Dejan Reljic (Nature Portfolio, 2021)
Abstract Physical activity is a cornerstone in the treatment of obesity and metabolic syndrome (MetS). Given the leading physical activity barrier of time commitment and safety concerns about vigorous exercise in high-risk groups, this study aimed to investigate the effects of two extremely time-efficient training protocols (< 30 min time effort per week), either performed as high- (HIIT) or moderate-intensity interval training (MIIT) over 12 weeks, in obese MetS patients. In total, 117 patients (49.8 ± 13.6 years, BMI: 38.2 ± 6.2 kg/m2) were randomized to HIIT (n = 40), MIIT (n = 37) or an inactive control group (n = 40). All groups received nutritional counseling to support weight loss. Maximal oxygen uptake (VO2max), MetS severity (MetS z-score), body composition and quality of life (QoL) were assessed pre-and post-intervention. All groups significantly reduced body weight (~ 3%) but only the exercise groups improved VO2max, MetS z-score and QoL. VO2max (HIIT: + 3.1 mL/kg/min, p < 0.001; MIIT: + 1.2 mL/kg/min, p < 0.05) and MetS z-score (HIIT: − 1.8 units, p < 0.001; MIIT: − 1.2 units, p < 0.01) improved in an exercise intensity-dependent manner. In conclusion, extremely low-volume interval training, even when done at moderate intensity, is sufficiently effective to improve cardiometabolic health in obese MetS patients. These findings underpin the crucial role of exercise in the treatment of obesity and MetS.